Depredación de Lithobates psilonota (Anura: Ranidae) por Leptodeira splendida bressoni (Squamata: Colubridae) en arroyos del área natural protegida Sierra de Quila, Jalisco, México - Huerta-García, Eduardo; Rosas-Espinoza, Verónica Carolina; Santiago-Pérez, Ana Luisa; Godoy-González, Arquímedes Alfredo; Arreola-Aguirre, Jachar; Ayón-Escobedo, A. Alberto (Instituto de Ecología, A.C., 2015)
Photographic evidence shows the first record of predation in Mexico of Lithobates psilonota by Leptodeira splendida bressoni in the natural protected area Sierra de Quila, Jalisco.